Mycoplasma ovipneumoniae-derived lipid-associated membrane proteins induce cytokine secretion in mouse peritoneal macrophages through TLR2 signalling. (October 2020) - Bai, Fan; Wu, Jindi; Liu, Bo; Wang, Xiaohui; Shi, Xiaona; Lv, Tianxing; Wang, Yanfang; Hao, Yongqing
Abstract: Background: Mycoplasma ovipneumoniae (M. ovi) is the causative agent of chronic non-progressive pneumonia in sheep, goats, bighorn, and wild small ruminants. However, the mechanism of infection and immune response to M. ovi remain unclear. Invading microbes express lipid-associated membrane proteins (LAMPs) on the cell surface that interact with host cells to facilitate infection, and are thus the major molecules recognised by the host immune system. Upon LAMP recognition, Toll-like receptor 2 (TLR2) and NLRP3 inflammasome sense the pathogens and signalling pathways for cytokine secretion. In this study, we investigated whether M. ovi and M. ovi -derived LAMPs are immuno-biologically active compounds capable of activating mouse peritoneal macrophages and explored the underlying mechanism. Results: After infection of wild-type mice with M. ovi, the expression of TLR2 and NLRP3 at the transcriptional and translational levels was determined with reverse transcription-polymerase chain reaction and flow cytometry. In addition, the cytokine levels and associated pathways were detected in infected wild-type, Tlr2 −/−, and Nlrp3 −/− mice via enzyme-linked immunosorbent assays and western blotting. The nuclear factor (NF)-κB and mitogen-activated protein kinase (MAPK) signalling pathways were found to mediate the expression of inflammatory cytokines in M. ovi or M. ovi -derived LAMP-infected peritoneal macrophages, and cytokines were not induced in Tlr2 −/− and/or Nlrp3 −/− macrophages. Conclusion: Host cytokine production is activated in response to M. ovi -derived LAMPs through the NF-κB and MAPK signalling pathway via TLR2. Highlights: M. ovi -derived LAMPs induce inflammatory cytokine production. The MAPK pathway mediates inflammatory cytokine expression. M. ovi and M. ovi -derived LAMPs activate mouse peritoneal macrophages.